Emergency use of nebulized milrinone, a phosphodiesterase 3 inhibitor, in status asthmaticus: a case report in Suriname - Bihariesingh-Sanchit, Rosita; Thakoersing, Ravikant; Bansie, Rakesh; Bihariesingh, Inhya (Brazilian Journal of Case Reports, 2023)
Data indicate the benefits of phosphodiesterase inhibitors as an add-on treatment in severe asthma, but mainly because of the limited tolerability, no compound reaches the market. Low- and middle-income countries (LMIC) face the challenge of successfully treating status asthmaticus, due to little or no access to expensive drug regimens. We describe a case of a 25-year-old man admitted to the ICU with status asthmaticus where nebulized milrinone was used as a last resort as there was no improvement with optimal standard management. After initiation of nebulized milrinone the patient could be smoothly weaned from ventilation and discharged.